1993
DOI: 10.1002/cne.903310106
|View full text |Cite
|
Sign up to set email alerts
|

Hair cell regeneration after streptomycin toxicity in the avian vestibular epithelium

Abstract: Recent reports documented the ability of the posthatch avian vestibular epithelia to produce hair cells continually at a low rate. This project was designed to investigate whether, in addition, the chicken vestibular system is capable of regenerating its sensory epithelium in response to a lesion. Aminoglycoside injections were given to young birds in order to damage the vestibular epithelium. Tritiated thymidine injections were used to label cells produced in response to the lesion. Treatment and age-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
142
5
3

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(157 citation statements)
references
References 52 publications
6
142
5
3
Order By: Relevance
“…For example, in chicks the VCR was reported to have recovered by 2-3 weeks following systemic administrations of streptomycin, a significantly shorter time course than that observed for head stability in our adult pigeons (Goode et al 1999). However, in chicks, the total horizontal semicircular canal hair cell density was noted to be near normal values (Goode et al 1999), although type I hair cells remained reduced in number (Goode et al 1999;Weisleder and Rubel 1993). In contrast, in pigeons regenerating following intralabyrinthine streptomycin applications, hair cell densities were reported to be only 30% of normal in the otolith organs , similar to the qualitative SEM hair cell density counts observed in the present study.…”
Section: Behavioral Recovery During Regenerationmentioning
confidence: 58%
See 2 more Smart Citations
“…For example, in chicks the VCR was reported to have recovered by 2-3 weeks following systemic administrations of streptomycin, a significantly shorter time course than that observed for head stability in our adult pigeons (Goode et al 1999). However, in chicks, the total horizontal semicircular canal hair cell density was noted to be near normal values (Goode et al 1999), although type I hair cells remained reduced in number (Goode et al 1999;Weisleder and Rubel 1993). In contrast, in pigeons regenerating following intralabyrinthine streptomycin applications, hair cell densities were reported to be only 30% of normal in the otolith organs , similar to the qualitative SEM hair cell density counts observed in the present study.…”
Section: Behavioral Recovery During Regenerationmentioning
confidence: 58%
“…These extrastriola and peripheral regions in birds have a much higher concentration of type II receptor cells compared with type I cells ( . Type II cells have repeatedly been shown to regenerate faster than type I cells (Carey et al 1996;Goode et al 1999;Kevetter et al 2000;Masetto and Correia 1997;Weisleder and Rubel 1993).…”
Section: Vestibular Receptor Damage and Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have demonstrated ongoing cell proliferation in mature vestibular organs (Jørgensen and Mathiesen, 1988;Roberson et al, 1992;Weisleder and Rubel, 1993;Rubel et al, 1995;Kil et al, 1997;Wilkins et al, 1999) and have demonstrated that the baseline level of proliferation appears to be counterbalanced by ongoing hair cell death (Kil et al, 1997;Goodyear et al, 1999;Stone et al, 1999;Wilkins et al, 1999). This dynamic pattern of ongoing cell death and proliferation differs from that observed in the chicken cochlea, in which the supporting cells are mitotically quiescent until the hair cells are lost because of trauma (Corwin and Cotanche, 1988; or proliferate at a very low rate .…”
Section: Relationship Between Spontaneous Hair Cell Death and Ongoingmentioning
confidence: 95%
“…Hair cells dying in an apoptotic-like manner participate in an active, organized cellular degradation and disposal with preserved tissue integrity and minimal inflammatory response (Li et al 1995;Lang and Liu 1997;Forge and Li 2000). Such preservation of the architecture of the sensory epithelium (SE) is crucial in order to retain organ function, particularly in tissues where hair cells are continuously produced throughout life (Weisleder and Rubel 1993;Kil et al 1997;Williams and Holder 2000).…”
Section: Introductionmentioning
confidence: 99%